THE IMPACT OF MACROECONOMICS AND MICROECONOMICS VARIABLES ON STOCK MARKET RETURNS: A COMPARATIVE STUDY ON EGYPTIAN AND GERMAN MARKET (Lex localis - Journal of Local Self-Government, 2025)
This study investigates how macroeconomic and microeconomic variables influence stock market returns in Egypt as an emerging country and Germany as a dveloped country. Using companies data, macroeconomic indicators and panel models, it examines inflation, exchange rate, interest rate, debt to equity rato, quick ratio and dividend per share. The findings show that broad economic conditions explain most of variation in returns, 41.8% in Egypt, and 51.3% in Germany. Inflation affects both markets differently, exchange rates boost returns,  while increasing interest rates affect egypt more. Microeconomic factors have limited effects with debt to equity and liquidity showing partial signifcance. Overall, the findings highlight how different economic conditions shape the stock market returns.